“WELL, IMAGINE, I’VE BEEN SLAUGHTERING IN WOOD FOR SEVERAL YEARS…”. WAR DRAWINGS, “SLAUGHTERED” MONUMENTS AND “EXECUTED” PAINTINGS BY LEOPOLD BUCZKOWSKI - Nader, Luiza (Prace Polonistyczne, 2024)
The text is an attempt at an analysis of the wartime paintings from the 1940s, the wooden sculptures conceived from the end of the 1960s and the so called “abstract paintings” by Leopold Buczkowski from a perspective of violence, brutality and trauma. The article examines themes, motifs, and traces of the Holocaust. Reflecting on Buczkowski’s visual works, the author makes reference to his literary oeuvre, the shifting cultural and historical frame, as well as to the distinction between the mimetic and the anti-mimetic paradigms of thinking about trauma proposed by Ruth Leys. Analyzing Buczkowski’s drawings, sculptures, and paintings, the author differentiates between those created from the position of an observer’s liminal experience and those created from the depths of the traumatic wound.